The Influence of The Power of Two Learning Model Containing Science Literacy on Students Learning Competencies in the Material of Human Digestive Systems in SMP Negeri 18 Padang - Sari Yulianti; Moralita Chatri; Relsas Yogica; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2019)
ABSTRACTThis research is based on the problems that exist in SMPN 18 Padang, students learning competencies are still low. Efforts that can be made are applying the learning model Power of Two with scientific literacy on digestive system material at SMPN 18 Padang. The purpose of this study was to determine the increase in the competency of students through the model The power of twowith scientific literacy in the material of human digestive systems in SMPN 18 Padang.This type of research is experimental research with a randomized control group posttest only design. The population in this study were all class VIII SMPN 18 Padang registered in the 2018/2019. Sampling was done using technique Simple Random Sampling, which was chosen as the sample of the study was class VIII.6 as the experimental and  VIII.7 as the control class. The instruments used were in the form of questions posttest for knowledge competencies, observation sheets for attitude and skills. The hypothesis was tested using the t-test, can be concluded that the competence of learners knowledge tcount 5,72> ttable 1.67, the competence of attitude  value tcount 1,84> ttable 1,67, and the competency of skills value tcount 3.39> ttable 1.67. This shows that the hypothesis is accepted. Concluded that the application of model The power of two with scientific literacy can improve the competency of knowledge, attitudes, and skills of class VIII students of SMPN 18 Padang. Keywords: the power of two,  scientific literacy, learning competency